Comparative Study of Structural, Morphological and Humidity Sensing Properties of Pure WO3 and Cu2O-WO3 Nanocomposite - Kumar Pandey, Narendra; Singh, Sanchita; Gupta, Priya (Asian Journal of Chemistry, 2020)
This work reports the enhancement of humidity sensing properties of tungsten trioxide (WO3) by the formation of nanocomposite with cuprous oxide (Cu2O). A 0.1 g of Cu2O was mixed with 0.9 g of WO3. Pellets of pure WO3 and the obtained mixture are prepared at pressure of 250 MPa applied for 0.5 h. The pellets were then annealed at 300 ºC, 400 ºC, 500 ºC and 600 ºC. X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyzed the crystallinity and morphology of as-prepared pellets surface. Humidity sensing application of pellets is studied in a specially designed chamber. It is observed that as relative humidity increases, there is decrease in the resistance of the pellets. The humidity-sensing investigation (10-99%RH) showed that the nanocomposite of Cu2O with WO3 annealed at 600 ºC, is having the best sensitivity, low hysteresis, less ageing and high reproducibility than pure WO3. It is also observed that as annealing temperature increases from 300 to 600 ºC, sensitivity increases. The present investigation could be useful for fabrication of resistive type humidity sensors for commercial applications.